Kochankowie - Skalski, Rafał (Poland : HBO Central Europe, 2009)
"For him I'm a woman, not a wheel chair," says one of the characters featuring in Rafał Skalski's documentary when describing the relationship between her, a woman with mobility problems, and her partner. The film is a story of love, attachment and a life together with a disabled person, which is not much different from the life of healthy couples. They have the same dreams, needs and desires. They plan their future together, furnish a new flat, go dancing and travel. They are not ashamed of talking about their intimacy and discussing their sexual activity in a remarkably open way. Like every relationship, they also encounter problems that are not always caused by disability.
Keywords: Poland